Copy Number Variations Analysis Identifies QPRT as a Candidate Gene Associated With Susceptibility for Solitary Functioning Kidney - Zhou, Xiao Y.; Zheng, Hao Y.; Han, Li; Wang, Yan; Zhang, Li; Shu, Xiao M.; Zhang, Mu L.; Liu, Guan N.; Ding, Lian S. (Frontiers in Genetics, 2021)
Background The lack of understanding of molecular pathologies of the solitary functioning kidney restricts the nephrologist to improve and strengthen the continuity between pediatric and adult nephrological care. Copy number variations (CNVs) account for a molecular cause of solitary functioning kidney, but characterization the pathogenic genes remains challenging. Methods In our prospective cohort study, 99 fetuses clinically diagnosed with a solitary functioning kidney were enrolled and evaluated using chromosomal microarray analysis (CMA). The genetic drivers for the pathogenic CNVs were analyzed. We characterized QPRT localization in fetal kidneys using immunohistochemistry and its expression in adult kidneys using quantitative RT-PCR. Further, QPRT was knocked down using siRNA in human embryonic kidney (HEK293T) cells, and the cell cycle and proliferation were tested. Results Besides one Triple X syndrome and one Down syndrome, we identified a total of 45 CNVs out of 34 subjects. Among the 14 pathogenic CNVs, CNV 16p11.2 hits the highest number of records with the phenotype of kidney anomalies in the Decipher database. Among the 26 genes within the 16p11.2 region, as a key enzyme for nicotinamide adenine dinucleotide (NAD+) biosynthesis, QPRT was distinctly localized in renal tubules whereas being barely observed in renal interstitial and glomeruli in fetal kidneys. The loss of QPRT prevented cells efficient transition into S phase, affected cell-cycle progression, and abrogated proliferation of human embryonic kidney cells. Conclusions Our data suggest that QPRT is a candidate gene associated with susceptibility for solitary functioning kidney. The CNVs discovered in our study exhibits great potentials for future applications in genetic counseling and pregnancy management.